2024
DOI: 10.1002/mabi.202300389
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic‐Loaded Ultrahigh Molecular Weight Polyethylenes

Sashank Lekkala,
Nicoletta Inverardi,
Jean Yuh
et al.

Abstract: The occurrence of periprosthetic joint infections (PJI) after total joint replacement constitutes a great burden for the patients and the healthcare system. Antibiotic‐loaded polymethylmethacrylate (PMMA) bone cement is often used in temporary spacers during antibiotic treatment. PMMA is not a load‐bearing solution and needs to be replaced by a functional implant. Elution from the ultra‐high molecular weight polyethylene (UHMWPE) bearing surface for drug delivery can combine functionality with the release of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Based on the antibiotic susceptibility data from the three different infection models, a high initial dosing of antibiotics (>100 × MIC) is required during the early stages of infection that should be sustained for a prolonged period irrespective of the susceptibility profiles of the bacterial strain. Antibiotic-loaded implant materials that have been developed to locally release high antibiotic concentrations in a sustained manner could be best suited for this application [60][61][62]. For inherently resistant infections, it is advisable to use stronger tools such as the synergistic use of antibiotic and non-antibiotic compounds to enhance the antibacterial activity as early as possible to achieve effective eradication [36,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the antibiotic susceptibility data from the three different infection models, a high initial dosing of antibiotics (>100 × MIC) is required during the early stages of infection that should be sustained for a prolonged period irrespective of the susceptibility profiles of the bacterial strain. Antibiotic-loaded implant materials that have been developed to locally release high antibiotic concentrations in a sustained manner could be best suited for this application [60][61][62]. For inherently resistant infections, it is advisable to use stronger tools such as the synergistic use of antibiotic and non-antibiotic compounds to enhance the antibacterial activity as early as possible to achieve effective eradication [36,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…10−15 Leveraging the UHMWPE component in total joint replacement as a delivery device has recently emerged as a potential avenue of investigation. 16,17 In previous studies, it was shown that UHMWPE can be loaded with analgesics to treat postoperative pain and provide prophylaxis against periprosthetic joint infection (PJI). 18−20 Specifically, bupivacaine-loaded UHMWPE implants could release clinically relevant drug doses for pain management in the immediate postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Local drug delivery and delivery systems for nonopioid analgesics and NSAIDs may enhance their benefits by increasing the bioavailability of the drugs at the targeted site while decreasing systemic exposure. Leveraging the UHMWPE component in total joint replacement as a delivery device has recently emerged as a potential avenue of investigation. , In previous studies, it was shown that UHMWPE can be loaded with analgesics to treat postoperative pain and provide prophylaxis against periprosthetic joint infection (PJI). Specifically, bupivacaine-loaded UHMWPE implants could release clinically relevant drug doses for pain management in the immediate postoperative period . Clinically, intraarticular bupivacaine is widely used as a bolus injection and in a sustained-delivery formulation (Exparel, Pacira Pharmaceuticals, CA) to effectively manage postoperative pain associated with total joint replacement .…”
Section: Introductionmentioning
confidence: 99%